Keeping the people's liberties : legislators, citizens, and judges as guardians of rights - Dinan, John J. (University Press of Kansas, 1998)
Which branch of government should be entrusted with safeguarding individual rights? Conventional wisdom assigns this responsibility to the courts, on the grounds that liberty can only be protected through judicial interpretation of bills of rights. In fact it is difficult for many people even to conceive of any other way that rights might be protected. John Dinan challenges this understanding by tracing and evaluating the different methods that have been used to protect rights in the United States from the founding until the present era. By analyzing the relative ability of legislators, citizens, and judges to serve as guardians of rights, Dinan's study demonstrates that each is capable of securing certain rights in certain situations.
Keywords: Universidad Sergio Arboleda; Civil rights -- United States.; Civil rights -- United States -- States.; Judicial power -- United States -- States.; Legislative power -- United States -- States.; Constituent power -- United States -- States.; United States -- Politics and government.; Droits de l'homme -- États-Unis.; Droits de l'homme -- États-Unis -- États.; Pouvoir judiciaire -- États-Unis -- États.; Pouvoir constituant -- États-Unis -- États.; États-Unis -- Politique et gouvernement.; LAW -- Legal History.; Civil rights; Civil rights -- U.S. states; Constituent power -- U.S. states; Judicial power -- U.S. states; Legislative power -- U.S. states; Politics and government; United States; Grundrechtsschutz; USA; Grondrechten.; Wetgeving.; Rechtspraak.; Burgers.; Politique et gouvernement -- États-Unis -- États.; Pouvoir legislatif -- États-Unis.; Pouvoir judiciaire -- États-Unis.; Droits civils et politiques -- États-Unis.; Pouvoir constituant -- États-Unis.; Legal history